2001
DOI: 10.1002/mus.1085
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of excitability measures in sensory nerve

Abstract: A recently described method for recording multiple excitability parameters of human motor nerves has been adapted to the study of sensory nerves. The protocol measures stimulus-response behavior using two stimulus durations (from which the distribution of strength-duration time constants is estimated), threshold electrotonus to 100 ms polarizing currents, a current-threshold relationship (indicating inward and outward rectification), and the recovery of excitability following supramaximal activation. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
139
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 141 publications
(148 citation statements)
references
References 33 publications
7
139
1
1
Order By: Relevance
“…Neurophysiological assessment of nerve function was undertaken using conventional nerve conduction studies [14,26] and axonal excitability studies [12,27]. A Medelec Synergy system (Oxford Instruments, Oxfordshire, U.K.) was used for nerve conduction studies of upper and lower limb nerves.…”
Section: Clinical Assessment: Grading Of Neurotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Neurophysiological assessment of nerve function was undertaken using conventional nerve conduction studies [14,26] and axonal excitability studies [12,27]. A Medelec Synergy system (Oxford Instruments, Oxfordshire, U.K.) was used for nerve conduction studies of upper and lower limb nerves.…”
Section: Clinical Assessment: Grading Of Neurotoxicitymentioning
confidence: 99%
“…The median nerve was stimulated at the wrist with a reference electrode placed 10 cm distal over bone and compound sensory action potentials (CSAPs) were recorded from the second digit. Using established protocols [12,27], multiple excitability parameters were recorded, as in prior studies of oxaliplatin-induced neurotoxicity [8,15], as indirect measures of resting axonal membrane potential. The recovery of excitability following impulse conduction, marking the function of voltage-gated Na ϩ channels, was assessed with the parameters refractoriness and superexcitability, calculated as the percent change in threshold 2.5 msec and 7 msec after supramaximal stimulation [12,29,30].…”
Section: Clinical Assessment: Grading Of Neurotoxicitymentioning
confidence: 99%
“…17 Our study has reaffirmed that the tendency of excitability differences between motor and sensory axons within the human distal median nerve. 18 It is known that large myelinated sensory axons have a greater persistent sodium current than alpha motor axons, and also exhibit inward rectification. 17 This difference in excitability can explain why paresthesia develops in sensory nerves more often than does fasciculation or cramp in motor nerves in PNs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the pulse duration used in direct current peripheral nerve stimulators has some bearing on whether motor or sensory nerves are stimulated. In particular, a pulse duration of B 0.1 msec is suggested to stimulate motor neurons more selectively without undue sensory discomfort, 24 whereas a pulse duration of C 0.3 msec is considered to be more selective for sensory nerves, 12 although this distinction remains unclear in clinical practice. 25 The ICCs of the Stimpod at a frequency of 2 Hz and a pulse width of 0.3 msec fell within the ''good'' and ''excellent'' ranges of reproducibility for the second and fifth digits, respectively, potentially making this a useful combination of settings for CPT testing.…”
Section: Discussionmentioning
confidence: 99%